Analysis of Prospective Primary School Teachers’ Knowledge Regarding Chemical Representations on Crystallization Experiment - Melis Arzu Uyulgan; Nalan Akkuzu Güven (Universitas Pendidikan Indonesia, 2022)
The study aims to determine the subject matter knowledge of Prospective Primary School Teachers (PPSTs) and analyze their chemical representation levels on crystallization. The study was carried out with descriptive research with a qualitative approach based on this purpose. The study participants were eighty freshman students studying at the Department of Primary Education in a state university in the Aegean Region of Turkey. The data were collected using a worksheet containing seven open-ended questions regarding the crystallization experiment. The questions were about the solubility of salt in water, the formation of the salt water and its solubility-temperature graph, the formation of the saturated salt water, and the appearance of particles formed during crystallization. A worksheet was prepared to determine the chemical representation levels of the PPSTs, and the data were subjected to document analysis. The researchers conducted a demonstration experiment and an animated video on the extraction of table salt by crystallization as an activity during the study process. The results indicated that PPSTs' responses related to crystallization were mainly at the macroscopic level. At the same time, they had great difficulty explaining at the levels of sub-microscopic and symbolic representations.Moreover, they could not explain the concept of dissolution with scientific expressions and distinguish the mixtures from each other. Additionally, most prospective teachers could not draw the correct solubility-temperature graph, so they had difficulty in symbolic representations. The study results imply that to raise the quality of science education in Turkey, PPSTs must attend a quality teaching of science, so primary school students acquire scientifically accurate knowledge of the basic science subjects and concepts such as dissolution, solubility, and crystallization.